Toxoplasma GRA15 and GRA24 are important activators of the host innate immune response in the absence of TLR11 - Mukhopadhyay, Debanjan (PLoS Pathog, 2020)
The murine innate immune response against Toxoplasma gondii is predominated by the interaction of TLR11/12 with Toxoplasma profilin. However, mice lacking Tlr11 or humans, who do not have functional TLR11 or TLR12, still elicit a strong innate immune response upon Toxoplasma infection. The parasite factors that determine this immune response are largely unknown. Herein, we investigated two dense granule proteins (GRAs) secreted by Toxoplasma, GRA15 and GRA24, for their role in stimulating the innate immune response in Tlr11(-/-) mice and in human cells, which naturally lack TLR11/TLR12. Our results show that GRA15 and GRA24 synergistically shape the early immune response and parasite virulence in Tlr11(-/-) mice, with GRA15 as the predominant effector. Nevertheless, acute virulence in Tlr11(-/-) mice is still dominated by allelic combinations of ROP18 and ROP5, which are effectors that determine evasion of the immunity-related GTPases. In human macrophages, GRA15 and GRA24 play a major role in the induction of IL12, IL18 and IL1β secretion. We further show that GRA15/GRA24-mediated IL12, IL18 and IL1β secretion activates IFNγ secretion by peripheral blood mononuclear cells (PBMCs), which controls Toxoplasma proliferation. Taken together, our study demonstrates the important role of GRA15 and GRA24 in activating the innate immune response in hosts lacking TLR11.